Increased Level of Tim-3+PD-1+CD4+T Cells With Altered Function Might Be Associated With Lower Extremity Arteriosclerosis Obliterans - Cui, Liyuan; Chen, Lanting; Dai, Yuxin; Ou, JingMin; Qiu, Mingke; Wang, Songcun (Frontiers in Immunology, 2022)
Lower extremity arteriosclerosis obliterans (LEASO) is a vascular disease that may result in adult limb loss worldwide. CD4+T cell-mediated immunity plays a significant role in LEASO. The T cell immunoglobulin and mucin domain 3 (Tim-3) and inhibitory receptors programmed cell death-1 (PD-1) are well known immune checkpoints that play crucial roles in regulating CD4+T cell activation or tolerance. In this study, blood mononuclear cells were isolated from blood samples of healthy controls and patients who diagnosed LEASO for the first time (III or IV stage according to the Fontaine classification system, and had not received drug (except for heparin) or surgery treatment). We concluded the higher proportion of Tim-3+PD-1+CD4+T cells in human higher stage LEASO, and oxidized low density lipoprotein (ox-LDL) increased Tim-3 and PD-1 co-expression by activating CD4+T cells in a dose dependent manner. Tim-3+PD-1+CD4+T cells displayed a more active status and produced more anti-atherogenic cytokines compared to Tim-3-PD-1-CD4+T cells. Apart from the increased frequency, altered function of Tim-3+PD-1+CD4+T cells were also observed in LEASO compared to those from healthy controls. These in vitro results indicated that Tim-3 and PD-1 might be promising early warning targets of higher stage LEASO. In addition, blockade of Tim-3 and PD-1 signaling pathways aggravated the pro-atherogenic Th1 responses in LEASO, further suggesting that the cardiovascular safety must be a criterion considered in using immune checkpoint inhibitors to reverse T cell exhaustion during tumors and chronic viral infections.